2005
DOI: 10.1128/mcb.25.18.8259-8272.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human NDR Kinases Are Rapidly Activated by MOB Proteins through Recruitment to the Plasma Membrane and Phosphorylation

Abstract: Human nuclear Dbf2-related kinases (NDRs) are up-regulated in certain cancer types, yet their precise function(s) and regulatory mechanism(s) still remain to be defined. Here, we show that active (phosphorylated on Thr444) and inactive human NDRs are both mainly cytoplasmic. Moreover, NDR kinases colocalize at the plasma membrane with human MOBs (hMOBs), which are recently described coactivators of human NDR in vitro. Strikingly, membrane targeting of NDR results in a constitutively active kinase due to phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
187
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(201 citation statements)
references
References 22 publications
(50 reference statements)
13
187
1
Order By: Relevance
“…Their results with ours indicate that the phosphorylation of Mats/MOB1 by MSTs is conserved in human and fly. The molecular activation mechanism of NDR kinases is well studied in vitro and in vivo (Bichsel et al, 2004;Hergovich et al, 2005;Stegert et al, 2005Stegert et al, , 2006a. However, because of the presence of many isoforms, there is no report to directly discuss the involvement of MST2 and MOB1 in the activation of NDR1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results with ours indicate that the phosphorylation of Mats/MOB1 by MSTs is conserved in human and fly. The molecular activation mechanism of NDR kinases is well studied in vitro and in vivo (Bichsel et al, 2004;Hergovich et al, 2005;Stegert et al, 2005Stegert et al, , 2006a. However, because of the presence of many isoforms, there is no report to directly discuss the involvement of MST2 and MOB1 in the activation of NDR1.…”
Section: Discussionmentioning
confidence: 99%
“…MST2 phosphorylates LATS1 and 2 and activates them. MOB1 also binds NDR1 and 2 and induces the autophosphorylation (Bichsel et al, 2004;Hergovich et al, 2005). MST3 phosphorylates and activates NDR2 but fails to activate the MOB1-binding deficient NDR2 mutant (Stegert et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that hMOB1A and hMOB1B bind with LATS1/2 and NDR1/2 [45,[62][63][64][65][66][67][68][69][70]. However, it is unclear whether other members of the human MOB family also interact with LATS and NDR kinases.…”
Section: Interaction Of Hmobs With Lats/ndr Family Members In Vitromentioning
confidence: 99%
“…hMOB1B has been shown to bind to and activate the kinase activities of LATS1, LATS2, NDR1 and NDR2 at the plasma membrane upon phosphorylation by mammalian sterile-20 like (MST) kinases ( Figure 5) [23,45,[62][63][64][65][66]. hMOB1B interacts with NDR protein kinases at their conserved N-terminal regulatory domain, also known as the S100B-MOB association (SMA) domain.…”
Section: Mammalian Homologs Of Mobmentioning
confidence: 99%
See 1 more Smart Citation